Skin free flap for penile skin covering defect - Case report (2019)
Introduction Report the case of a patient with penile sclerosinglipogranuloma who was taken to corrrection of complex penile curvature with split-thickness graft with later secondary retraction that caused penile curvature preventing intercourse and during surgical mangement generated a skin coverge defect that required the use of free skin flap from the abdominal wall. Material and Methods 46 year old men with a history of surgical resection of sclerosinlipogranuloma in dorsal penile resected in 2006 and erectile dysfunction managed with intracavernous therapy with prostaglandin E2; that required abdominal skin grafts in 2 opportunities for skin defect coverage, with subsequent fibrosis and dorsal penile curvature of 60 degrees associated with pain during erection. Carried complex penile curvature correction in Hopsital Universitario Mayor - Méderi. Plication of the tunica albuginea with Yachia technique is performed until correction of dorsal curvature in 90%. Coverage defect area is identified, so that flap of hypogastric abdominal region is lifted and anchored in the distal edge of coverage defect. 6 weeks later is taken to second surgical procedure, with release and remodeling of the flap and anchorage of it in the proximal edge of the defect. 3 months after, the patient is reassessed finding complete coverage of the area on the dorsal surface of the penis. Erection is induced by intracavernousalprostadil showing dorsal penile curvature of less than 5 degrees. Discussion Patients with sclerosing penile lipogranuloma undergo plaques in penile layers that when resected may require the use of skin grafts or pedicle flaps for coverage in an area with high probability of ischemia in these tissues. In cases in which the graft contraction result in penile curvature, that in the event of preventing coitus require surgical correction thereof. The use of autologous grafts or allografts have shown satisfactory results, but may require two surgical procedures to obtain adecuate tissue. In patients in whom the penile skin is not enough to cover the defect, the second option is scrotal skin, which retains similar characteristics, as well as an excellent vascularization. When there is no adecuate scrotal skin, full thickness skin grafting as last option is used with satisfactory results. Conclusions Currently, the use of abdominal skin in these skin defects has no wide acceptance because of the presence of dermal annexes, ending in a suboptimal aesthetic appearance, however, it is evident in this case, is a tissue that is easily adapted to its new location and allows the latter, which is to achieve adequate organ receptor function. Copyright © 2019, Sociedad Colombiana de Urología. Publicado por Thieme Revinter Publicações Ltda., Rio de Janeiro, Brazil. Todos los derechos reservados.